IMPLEMENTASI NILAI TRI HITA KARANA DALAM PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DI SMP NEGERI 5 DENPASAR - Gusti Agung Ayu Made Seniwati; I Gusti Ayu Suasthi; Ni Made Indiani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study aims to examine 1) the value of Tri Hita Karana as a guideline in the Pancasila Student Profile Strengthening Project (P5) at SMP Negeri 5 Denpasar, 2) the process of implementing Tri Hita Karana values in the Pancasila Student Profile Strengthening Project (P5) at SMP Negeri 5 Denpasar, and 3) the implications of the implementation of Tri Hita Karana values in the Pancasila Student Profile Strengthening Project (P5) on the character of students at SMP Negeri 5 Denpasar. This type of research is descriptive qualitative research. Data were collected through a process of observation, interviews, and review of documents. The results of this study indicate that, (1) There are 3 factors that influence the value of Tri Hita Karana as a guideline in the Pancasila Student Profile Strengthening Project, including: philosophical factors, psychological factors, and pedagogical factors, (2) The implementation of Tri Hita Karana values in the Pancasila Student Profile Strengthening Project consists of three stages, namely: planning, implementation, and challenges of the Pancasila Student Profile Strengthening Project, and ((3) The implication of Tri Hita Karana value in the Pancasila Student Profile Strengthening Project, namely: character building of students based on local wisdom by implementing the value of Tri Hita Karana in the Pancasila Student Profile Strengthening Project which aims to produce a transformative millennial generation and the development of the Pancasila student profile character includes students who are faithful, devoted to God Almighty and have noble character, who are independent, critical reasoning, creative, mutual cooperation and gl obal diversity. Keywords: Tri Hita Karana, Pancasila Student Profile Strengthening Project, Character Education.